2019
DOI: 10.4103/jlp.jlp_39_19
|View full text |Cite
|
Sign up to set email alerts
|

Recent pattern of antibiotic resistance in Staphylococcus aureus clinical isolates in Eastern India and the emergence of reduced susceptibility to vancomycin

Abstract: PURPOSE: We aimed to determine the recent pattern of antibiotic resistance and assess the vancomycin susceptibility profile of clinical Staphylococcus aureus in view of emerging reports of vancomycin creep, reduced vancomycin susceptibility (RVS), including heterogeneous vancomycin-intermediate S. aureus (hVISA) and vancomycin-intermediate S. aureus, and vancomycin resistance in S. aureus isolates. MATERIALS AND METHODS: Consecutive, nonduplicate isolates of S. aureus between July 2015 and June 2016 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
0
10
2
Order By: Relevance
“…The levels of resistance to azithromycin and doxycycline were found to be 37.80%, while resistance to gentamicin was 22.05%. These levels were higher compared to Mohanty et al 26 . However, in our study we reported a lower resistance level to levofloxacin and ciprofloxacin compared to Mohanty et al (2019) who reported a higher resistance to ciprofloxacin (52.1%) 26 .…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The levels of resistance to azithromycin and doxycycline were found to be 37.80%, while resistance to gentamicin was 22.05%. These levels were higher compared to Mohanty et al 26 . However, in our study we reported a lower resistance level to levofloxacin and ciprofloxacin compared to Mohanty et al (2019) who reported a higher resistance to ciprofloxacin (52.1%) 26 .…”
Section: Discussioncontrasting
confidence: 55%
“…These levels were higher compared to Mohanty et al 26 . However, in our study we reported a lower resistance level to levofloxacin and ciprofloxacin compared to Mohanty et al (2019) who reported a higher resistance to ciprofloxacin (52.1%) 26 . For nitrofurantoin, the level of resistance was 19.96% which is comparable to 20% resistance reported by Hasan et al 27 .…”
Section: Discussioncontrasting
confidence: 55%
“… 10 Among the S. aureus , the overall MRSA prevalence in our study was 33.6% which was lower than studies from various centers across India where the prevalence rates vary from 38.6% to 52%. 15 16 17 Moreover, we observed that the MRSA prevalence rose from 29.5% in 2016 to 35% in 2018. This pattern was very similar to the recent reports which highlighted that over a decade, the MRSA prevalence has gradually escalated from 29% in 2009 18 to 39% in 2018.…”
Section: Discussionmentioning
confidence: 81%
“…ICMR reports 50% of nosocomial S. aureus as methicillin resistant in the year 2020 [ 16 ]. Few centers are now reporting high vancomycin MICs of 2 µg/mL (though classified as sensitive, this MIC is often associated with failure of therapy) [ 35 ]. The prevalence of vancomycin intermediate S. aureus (VISA) and vancomycin resistant S. aureus (VRSA) is low in India.…”
Section: Current Burden Of Antimicrobial Resistance In Indian Childrenmentioning
confidence: 99%